The need for more variety in Dutch spatial planning policies - The case of the Rotterdam Port - Marcel Van Gils; Menno Huys (European Regional Science Association (ERSA), 2005)
Airports and seaports in general serve as important nodes that connect national, regional and local areas with global networks. The balancing of the apparently contradictory spatial quality requirements of this multi-level and multi-actor environment is a challenge. The focus of this paper is on spatial quality requirements regarding the port region of Rotterdam. A well-known theory that can describe the rationale behind the need for balancing between localised and non-localised networks is Manuel Castells notion of the space of places and the space of flows in the network society. These concepts are taken as input for the case study about the port of Rotterdam. The non-localised (global) networks are dominated by Transnational Corporations that try to expand their revenues by optimising the logistic chain. Ports are nodes in this chain and are expected to offer effective and efficient throughput. On the other hand the national, regional and local environment in which the port is embedded puts other spatial claims on the port area. For making realistic policies regarding the future spatial development of a port it is of crucial importance that the different spatial quality requirements of the involved stakeholders are recognized. Only then it is possible to develop new ways of coping with the diverging claims. The mapping and analysis of the spatial quality requirements that come together in the port region of Rotterdam forms the main aim of this paper. The insights can be used when developing more sustainable and realistic policies for the future. The first step is to identify the main domains of spatial quality requirements. These can be roughly split in economic, social and ecological requirements. Then the perceptions of the main stakeholders regarding the future spatial quality of the Rotterdam port region shall be mapped on the basis of interviews and the study of policy documents. After the identification of the claims we look how is dealt with the different spatial claims in the policies regarding the port of Rotterdam. After this the authors consider the consequences of the outcomes for the Dutch seaport policy. Then it is possible to answer the question if the current policies deal adequately with the different claims. In the concluding paragraph some recommendations are presented to optimise the balance between localised and non-localised spatial quality requirements for the port of Rotterdam.
Keywords: 330